A treasury of modern mysteries - Christie, Agatha 1890-1976
Contiene: Endless nigth.-Norman and the Killer.-Kessler, the inside man.-The nine mile walk.-Cain's mark.-The purple is everrything.-The villa Marie Celeste.-Dont look now.-Never shake a family tree.-The reason.-Cottage for august.-The goodbye look.